Tecnologias de informação e comunicação, rede científica e inovação comunicacional: o caso do consórcio antiferrugem - Cabrera, Lilian Cervo (2012)
This paper examines a possible alternative for dissemination of information and communication technologies in rural areas. In this sense, aimed to analyse, evaluate and validate some statistics metrics generated by Google Analytics software to the site of the Consórcio Antiferrugem. The analysis considered the metrics generated for the period of June 30, 2007 to June 30, 2011, during which the site of the Consórcio Antiferrugem totaled four cropping season of soybeans. From the metric data of the tool in use, we sought to identify some kind of user profile and certain pattern of use of the site. The results indicate that the site proves to be an innovation communication, since it plays a mobilizing role in the formation of a scientific network in combating a plant disease. To achieve the objective proposed in this work, we chose to conduct a search of the exploratory case study. To conduct the study, sought to relate the data to access the site with the sowing dates for soybean, planting sites, weather forecasts and increases or decreases in the applications of fungicides in crops. In addition, there was an interview with creator and responsible for building the current site of the Consórcio Antiferrugem, plant pathologist and professor at UFRGS, Emerson Del Ponte. Data access within the site are presented nationally and then broken down to the states of Mato Grosso do Sul and Rio Grande do Sul, which had their individual statistical studies. The study revealed that it is difficult to determine exactly who in the soybean production chain accesses the site, if they are mostly researchers, extension workers, laboratory workers or farmers. However, it was possible to infer that their users are seeking technological information through the Internet, becoming key actors in the chain of soybeans. These actors are considered to be decision-makers in their regions, and disseminate information locally and this causes the main objective of the site of the Consórcio Antiferrugem is reached. Thus, the scientific network generated by the Consórcio Antiferrugem proves to be much higher than that measured by the number of accesses to the site, once face to face dialogue between the actors of the chain contributes to the dissemination of information about the disease and the occurrence of focuses on the regions.